Synthesis and Evaluation of Copper-Supported Titanium Oxide Nanotubes as Electrocatalyst for the Electrochemical Reduction of Carbon Oxide to Organics - Hossain, S. K. Safdar; Saleem, Junaid; Rahman, SleemUr; Zaidi, Syed Mohammed Javaid; McKay, Gordon; Cheng, C. K. (MDPI, 2019)
Carbon dioxide (CO2) is considered as the prime reason for the global warming effect and one of the useful ways to transform it into an array of valuable products is through electrochemical reduction of CO2 (ERC). This process requires an efficient electrocatalyst with high faradaic efficiency at low overpotential and enhanced reaction rate. Herein, we report an innovative way of reducing CO2 using copper-metal supported on titanium oxide nanotubes (TNT) electrocatalysts. The TNT support material was synthesized using alkaline hydrothermal process with Degussa (P-25) as a starting material. Copper nanoparticles were anchored on the TNT by homogeneous deposition-precipitation method (HDP) with urea as precipitating agent. The prepared catalysts were tested in a home-made H-cell with 0.5 M NaHCO3 aqueous solution in order to examine their activity for ERC and the optimum copper loading. Continuous gas-phase ERC was carried out in a solid polymer electrolyte (SPE) reactor. The 10% Cu/TNT catalysts were employed in the gas diffusion layer (GDL) on the cathode side with Pt-Ru/C on the anode side. Faradaic efficiencies for the three major products namely methanol, methane, and CO were found to be 4%, 3%, and 10%, respectively at −2.5 V with an overall current density of 120 mA/cm2. The addition of TNT significantly increased the catalytic activity of electrocatalyst for ERC. It is mainly attributed to their better stability towards oxidation, increased CO2 adsorption capacity and stabilization of the reaction intermediate, layered titanates, and larger surface area (400 m2/g) as compared with other support materials. Considering the low cost of TNT, it is anticipated that TNT support electrocatalyst for ECR will gain popularity